1993
DOI: 10.1021/bi00089a012
|View full text |Cite
|
Sign up to set email alerts
|

Endonexin (annexin IV)-mediated lateral segregation of phosphatidylglycerol in phosphatidylglycerol/phosphatidylcholine membranes

Abstract: Endonexin (annexin IV) is a member of the annexin family of homologous proteins that share the ability to bind to pure lipid membranes and to aggregate vesicles in a Ca(2+)-dependent fashion. Endonexin appears to preferentially interact with certain types of lipids such as phosphatidylglycerol (PG) in PG/phosphatidylcholine (PC) mixed lipid membranes. Such preferential binding should result in localization of PG lipids to membrane regions where endonexin is bound. This was tested using a PG derivative containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 18 publications
8
32
0
Order By: Relevance
“…To confirm the different interaction of the two b 5 forms with lipid domains, we applied an alternative method, based on fluorescence measurements of excimer formation coupled to the use of the pyrene-labeled fluorescent probes pyrene-PS or pyrene-PC inserted in POPC liposomes. Changes in excimer͞monomer intensity ratios induced by associated proteins can give information on the interactions of the proteins with the lipid probes or with the lipid domains that contain them (23).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the different interaction of the two b 5 forms with lipid domains, we applied an alternative method, based on fluorescence measurements of excimer formation coupled to the use of the pyrene-labeled fluorescent probes pyrene-PS or pyrene-PC inserted in POPC liposomes. Changes in excimer͞monomer intensity ratios induced by associated proteins can give information on the interactions of the proteins with the lipid probes or with the lipid domains that contain them (23).…”
Section: Resultsmentioning
confidence: 99%
“…These secondary DE calcium-binding sites could play a functional role, however, once the protein is bound to the membrane interface by transiently binding calcium and phospholipids and thus could contribute to reduce the global lateral diffusion of these two species (26,27). The consensus sequence for the equatorial PS-binding site was found exclusively in domain 1 or domain 2 but not in the other two domains.…”
Section: Discussionmentioning
confidence: 98%
“…This was unexpected based on earlier analyses, which have generally implied that the net entropy change should be negative for several reasons. Multiple studies have shown that membrane phospholipids are clustered (38,39) and/or immobilized (40, 41) upon binding of annexins, and the membrane becomes more rigid (42), all factors that should cause a reduction in entropy. Likewise, the formation of ordered multimeric complexes of annexin V on the vesicle surface (13, 18 -21) should also reduce entropy.…”
Section: Discussionmentioning
confidence: 99%